Activation of a Chimeric Rpb5/RpoH Subunit Using Library Selection - Sommer, Bettina (Public Library of Science, 2014)
Rpb5 is a general subunit of all eukaryotic RNA polymerases which consists of a N-terminal and a C-terminal domain. The corresponding archaeal subunit RpoH contains only the conserved C-terminal domain without any N-terminal extensions. A chimeric construct, termed rp5H, which encodes the N-terminal yeast domain and the C-terminal domain from Pyrococcus furiosus is unable to complement the lethal phenotype of a yeast rpb5 deletion strain (Δrpb5). By applying a random mutagenesis approach we found that the amino acid exchange E197K in the C-terminal domain of the chimeric Rp5H, either alone or with additional exchanges in the N-terminal domain, leads to heterospecific complementation of the growth deficiency of Δrpb5. Moreover, using a recently described genetic system for Pyrococcus we could demonstrate that the corresponding exchange E62K in the archaeal RpoH subunit alone without the eukaryotic N-terminal extension was stable, and growth experiments indicated no obvious impairment in vivo. In vitro transcription experiments with purified RNA polymerases showed an identical activity of the wild type and the mutant Pyrococcus RNA polymerase. A multiple alignment of RpoH sequences demonstrated that E62 is present in only a few archaeal species, whereas the great majority of sequences within archaea and eukarya contain a positively charged amino acid at this position. The crystal structures of the Sulfolobus and yeast RNA polymerases show that the positively charged arginine residues in subunits RpoH and Rpb5 most likely form salt bridges with negatively charged residues from subunit RpoK and Rpb1, respectively. A similar salt bridge might stabilize the interaction of Rp5H-E197K with a neighboring subunit of yeast RNA polymerase and thus lead to complementation of Δrpb5.